Analysis of the Roles of Social Capital and Behavioral Finance In Buwuh Tradition in Lowokwaru Sub-District of Malang City - Adelia Putri, Desta; Fitanto, Bahtiar (Journal of Development Economic and Social Studies, 2026)
The buwuh tradition is a form of mutual assistance through giving money or goods at celebrations. Initially perceived as a voluntary gift, buwuh has gradually shifted into a social obligation that is often recorded and treated as a form of debt. Despite rapid social change in urban areas, this tradition continues to persist in Lowokwaru District, Malang City, reflecting strong adherence to local social and cultural norms. This study aims to analyze the role of social capital and behavioral finance, particularly herding behavior, in shaping community participation in the buwuh tradition. The research employs a qualitative approach using Spradley’s ethnographic method. Data were collected through participant observation, structured interviews with community members across several villages in Lowokwaru District, and field documentation. Data analysis followed four ethnographic stages: domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The findings reveal that social capital plays a crucial role in sustaining the buwuh tradition through three key elements: norms, beliefs, and social networks. These elements create moral pressure that encourages continued participation. Furthermore, community involvement is strongly influenced by intentional herding behavior, where individuals consciously follow majority practices despite economic burdens to avoid social sanctions and maintain social harmony.